Given: Given the function: f(x) = (x − 3)(x + 7)(x − 1)
Required: its f-intercept and its x-intercepts.
Explanation:
![f(x)=(x-3)(x+7)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/hewbsv6rnv02chzjkoyxcqfrlk76oesj8h.png)
For f-intercept, put x = 0
![\begin{gathered} f(0)=(0-3)(0+7)(0-1) \\ f(0)=21 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3w3jbt275vykuyw1g159vgim26zkor1tn1.png)
So the f-intercept is (0,21).
For x-intercepts, put f(x) = 0
![\begin{gathered} 0=(x-3)(x+7)(x-1) \\ x=3,-7,1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y761gikpfbjywmb5k4t1h6tg2y728awlgw.png)
So x-intercepts are (3,0),(-7,0) and (1,0).
Final Answer:
f-intercept: (0,21)
x-intercept: (3,0),(-7,0),(1,0).